2014
DOI: 10.1161/atvbaha.114.303374
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Polyphenols Enhance High-Density Lipoprotein Function in Humans

Abstract: Objective-Olive oil polyphenols have shown beneficial properties against cardiovascular risk factors. Their consumption has been associated with higher cholesterol content in high-density lipoproteins (HDL). However, data on polyphenol effects on HDL quality are scarce. We, therefore, assessed whether polyphenol-rich olive oil consumption could enhance the HDL main function, its cholesterol efflux capacity, and some of its quality-related properties, such HDL polyphenol content, size, and composition. Approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
167
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(182 citation statements)
references
References 28 publications
12
167
1
2
Order By: Relevance
“…Moreover, PCs can modulate enzyme activities which may represent relevant antioxidant mechanisms by which dietary olive phenolic could have beneficial impact on cardiovascular health [21]. Phenol metabolites from olive have been observed to be incorporated to HDL particles where they could exert a local antioxidant protection and contribute to a functional enhancement of the HDL particle [22]. In concordance with these results, we observed that thyme phenols were also incorporated to HDL after FVOOT intervention and that olive phenol metabolites were higher after FVOO intervention compared to baseline and also to VOO.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PCs can modulate enzyme activities which may represent relevant antioxidant mechanisms by which dietary olive phenolic could have beneficial impact on cardiovascular health [21]. Phenol metabolites from olive have been observed to be incorporated to HDL particles where they could exert a local antioxidant protection and contribute to a functional enhancement of the HDL particle [22]. In concordance with these results, we observed that thyme phenols were also incorporated to HDL after FVOOT intervention and that olive phenol metabolites were higher after FVOO intervention compared to baseline and also to VOO.…”
Section: Discussionmentioning
confidence: 99%
“…Several have suggested increased CEC with diets enriched in polyphenols 37 and alcohol intake 38 and no effect with unsaturated fat. 39,40 Only one small study testing exercise and CEC had a control arm, 41 suggesting no improvement with exercise training among patients with DM.…”
Section: Cec and Lifestyle Interventionsmentioning
confidence: 99%
“…In experimental studies, hydroxytyrosol is one of the strongest antioxidant, antiproliferative, proapoptotic, antiplatelet, and anti-inflammatory polyphenols (16). In addition, several clinical trials have shown the benefits of hydroxytyrosolrich olive oils on risk factors for CVD (11,12,17,18). Circulating biomarkers are always subject to some degree of homeostasis, absorption, distribution, or metabolism.…”
Section: Introductionmentioning
confidence: 99%